Jeux de trompe-l’œil dans une cité déchue : La Nouvelle-Orléans de George Washington Cable dans Old Creole Days - Valérie CROISILLE (E-REA)
Throughout his work, 19th century writer George Washington Cable, who was born in New Orleans, kept describing his native city with a tender and yet ruthless eye, before being almost forced into exile for having sharply turned his pen to a critique of his Creole fellow citizens. His story collection Old Creole Days (1879) is in between historical testimony and artistic work. Drawing from oral popular culture, it was largely inspired by local archives, as Cable, once a journalist, conscientiously skimmed them before drafting his tales. Far from merely focusing on the romantic character of New Orleans, on its old-fashioned charm and bygone glory, Cable’s satirical outlook probes the rusty mechanisms of a moribund society that revels in often devastating gossip, is plagued by prejudice and obsessed with a hierarchical conception of race. The issue of misused identity and sham, that is central in several stories of the collection, is related to the question of look – the look of the writer at his city and its inhabitants, the look of the characters at themselves and others, the frequent voyeuristic tendency of the protagonists and narrators. Look is omnipresent in the story collection, as though in New Orleans people, objects and places were constantly scrutinized through an often deficient sight that produces a distorted, yet highly subjective image of reality. How does the collapsing Creole society that fails to look beyond the limits it has set for itself make New Orleans a misfit city, whose inhabitants have sacrificed essence for appearance, in a never-ending game of make-believe, shams and dramatic turns of events that are the real thrill of Cable’s fiction ?